Co-Torrefaction Progress of Biomass Residue/Waste Obtained for High-Value Bio-Solid Products - Abdul Waheed; Salman Raza Naqvi; Imtiaz Ali (Energies, 2022)
The co-torrefaction of several biomasses may be a viable solution in the study area, as it produces biofuels and addresses waste-treatment concerns. This review evaluates biomass through ultimate, proximate, and FTIR analyses, and the mechanism of the co-torrefaction process is observed for product quality with a synergistic effect. Furthermore, the parameters of co-torrefaction, including temperature, reaction time, mass yield, energy yield, and the composition of the H/C and O/C ratio of the co-torrefied materials, are similar to those for coal composition. Different reactor types, such as fixed-bed, fluidized-bed, microwave, and batch reactors, are used for co-torrefaction, in which biomass blends with optimized blend ratios. The co-torrefaction process increases the bio-solid yield and heating value, the capacity to adsorb carbon dioxide, and the renewable fuel used for gasification. One of the objectives of this study is to adopt a process that must be viable, green, and sustainable without generating pollution. For this reason, microwave co-torrefaction (MCT) has been used in many recent studies to transform waste and biomass materials into an alternative fuel using a microwave reactor.